Biblical stewardship and electricity management in Ghana - V.S. Gedzi; E.K.E. Antwi (Acta Theologica, 2025)
The article discusses managerial challenge in Ghana’s electricity sector. The analysis relies on field interviews and general observation, supplemented by extensive reviews of related literature, including annual reports by sector managers and energy access data available on the web. The article finds that, over the years, the sector was not well managed, due to government’s appointments of party affiliates instead of those who do qualify to manage it. Noncommittal of sector managers has led to less productivity and less generation of energy. Even in a situation where there is enough generation, high levels of technical and non-technical losses reduce supply. The situation is worsened by high cost of production, and obsolete infrastructure caused by inability of sector managers to raise necessary capital, in order to invest in the sector. The article proposes how the incorporation of the biblical concept of “stewardship” into the theory of electricity management might help address the challenge.